Outcomes of Primary Radiosurgery Treatment of Glomus Jugulare Tumors: Systematic Review With Meta-analysis. Issue 9 (October 2018) - Shapiro, Scott; Kellermeyer, Brian; Ramadan, Jad; Jones, Garret; Wiseman, Brian; Cassis, Adam
Abstract : Objective: 1) Determine tumor control, symptomatic control, and complication rates of primary radiosurgery (PRS) for treatment of glomus jugulare tumors (GJTs) via systematic review and meta-analysis. 2) Identify risk factors for these outcomes. Data Sources: 1) Search of English articles in PubMed, Web of Science, Cochrane, and EBSCOhost databases from January 1950 to August 2017. Study Selection: Inclusion criteria: 1) treated GJT patients who had no previous treatment with radiosurgery, 2) follow-up with magnetic resonance imaging for at least 12 months, 3) reported pre and posttreatment symptoms, tumor control, or complications for individual PRS patients or for PRS patients as a cohort. Data Extraction: The following were extracted: number of patients, level of evidence, mean age, mean pretreatment tumor volume, tumor control rate, criteria for change in tumor size, symptom control rate, and complications. At the individual patient level the following were extracted: age, number of treatment fractions, total radiation dose to tumor margin, pretreatment tumor volume, Fisch or Glasscock–Jackson stage, pre- and posttreatment symptoms, tumor control, symptom control/improvement, length of follow-up, and complications. Data Synthesis: Fifteen studies encompassing 91 patients met criteria. Tumor control was achieved in 92% of patients, symptom control in 93%, and complications occurred in 8%. There was one major complication. Smaller tumor volume predicted improvement in symptoms with PRS. Conclusions: In the short term, PRS is safe and effective at controlling growth and clinical symptoms for patients with GJTs, though there exists significant selection bias, inconsistent reporting, and clinical heterogeneity among existing studies.